2016
DOI: 10.1002/anie.201610836
|View full text |Cite
|
Sign up to set email alerts
|

Native Top‐Down Mass Spectrometry of TAR RNA in Complexes with a Wild‐Type tat Peptide for Binding Site Mapping

Abstract: Ribonucleic acids (RNA) frequently associate with proteins in many biological processes to form more or less stable complex structures. The characterization of RNA–protein complex structures and binding interfaces by nuclear magnetic resonance (NMR) spectroscopy, X‐ray crystallography, or strategies based on chemical crosslinking, however, can be quite challenging. Herein, we have explored the use of an alternative method, native top‐down mass spectrometry (MS), for probing of complex stoichiometry and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…Thus IRMPD generally cleaves noncovalent before covalent bonds, 102 unless the energy required for noncovalent bond cleavage exceeds that for covalent bond cleavage. 53 , 103 Using energies (25% laser power, 180 ms irradiation time) that were sufficient for covalent bond cleavage in 59% of the (M – 2H + 4Na) 2+ ions from ESI and 27% dissociation of the (M + 2H) + ˙ ions from ECD of (M + 2H) 2+ ions resulted in only ∼15% dissociation of the (M – H + 4Na) 2+ ˙/(M – 2H + 4Na) 2+ ions. Out of the ∼15% dissociation products, 11.1% were losses of NH 3 , H 2 O, and H 3 PO 4 from covalent bond cleavage in (M – H + 4Na) 2+ ˙/(M – 2H + 4Na) 2+ ions, and only 3.9% were c , z ˙ or c ˙, z fragments ( b and y fragments from dissociation of the 7.7% nonradical (M – 2H + 4Na) 2+ ions were not observed).…”
Section: Resultsmentioning
confidence: 99%
“…Thus IRMPD generally cleaves noncovalent before covalent bonds, 102 unless the energy required for noncovalent bond cleavage exceeds that for covalent bond cleavage. 53 , 103 Using energies (25% laser power, 180 ms irradiation time) that were sufficient for covalent bond cleavage in 59% of the (M – 2H + 4Na) 2+ ions from ESI and 27% dissociation of the (M + 2H) + ˙ ions from ECD of (M + 2H) 2+ ions resulted in only ∼15% dissociation of the (M – H + 4Na) 2+ ˙/(M – 2H + 4Na) 2+ ions. Out of the ∼15% dissociation products, 11.1% were losses of NH 3 , H 2 O, and H 3 PO 4 from covalent bond cleavage in (M – H + 4Na) 2+ ˙/(M – 2H + 4Na) 2+ ions, and only 3.9% were c , z ˙ or c ˙, z fragments ( b and y fragments from dissociation of the 7.7% nonradical (M – 2H + 4Na) 2+ ions were not observed).…”
Section: Resultsmentioning
confidence: 99%
“…This is quite surprising in view of the high stability of guanidinium–phosphate interactions in gaseous ions and the inherent advantages of native MS, for example, that it does not require stable isotope labeling or crystallization, is not limited by crosslinking reactivity, and uses only relatively small quantities of sample material compared with NMR spectroscopy and X‐ray crystallography. Moreover, a number of laboratories have reported that in the gas phase, the strength of noncovalent bonds between RNA or deoxyribonucleic acid (DNA) and basic ligands can even exceed those of covalent bonds. As a case in point, we have recently shown that the noncovalent bonds between trans‐activation responsive (TAR) RNA and a peptide with the arginine‐rich binding region of the trans‐activator of transcription (tat) protein from HIV‐1 are sufficiently strong to survive phosphodiester backbone cleavage of the RNA by collisionally activated dissociation (CAD), which thus allowed its use to probe tat binding sites of TAR RNA by top‐down MS …”
Section: Introductionmentioning
confidence: 99%
“…The unusual stability of noncovalent bonds in the gas phase has been attributed to strong electrostatic interactions, such as salt bridges, ionic and neutral hydrogen bonds, and charge–dipole interactions, of which salt bridges were thought to provide the highest contribution to stability . In support of this hypothesis, calculations suggest that the interaction energy between guanidine and trifluoroacetic acid, that is, the stabilization achieved when the two neutral molecules are brought from infinite distance to equilibrium distance, is ≈70 kJ mol −1 , whereas that of protonated guanidine and trifluoroacetate, that is, the stabilization achieved when the two oppositely charged ions are brought from infinite distance to equilibrium distance, is ≈500 kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…10,12,13 Besides, we anticipate a potential use of the large SI labelled RNAs in recently reported mass spectrometric methods to localize protein binding sites, which give valuable information for the 3D structure modelling of large RNP particles. 31,32 We currently also focus on the synthesis of per-deuterated RNA building blocks. The building blocks will be beneficial for NMR but also for SAXS/SANS studies in an integrative structural biology approach, as the chemical RNA synthesis allows full control over segmental deuteration.…”
Section: -13mentioning
confidence: 99%